The submerged prolongation of Islands' land masses. The particular case of islands located in active spreading mid-oceanic ridges settings - Madureira, Pedro (2020)
From the articulation of articles 121 (2) and 76 of the United Nations Convention on the Law of the Sea (UNCLOS), islands from a coastal State are entitled to a continental shelf, to be determined in the same way as for any other land territory. UNCLOS defines the continental shelf of a coastal State in relation to its continental margin. Article 76 (3) defines the continental margin in terms of the submerged prolongation of the land mass of the coastal State, irrespectively of the nature of the crust that supports that land mass. This concept of crustal neutrality is also supported in paragraph 7.2.9 of the Scientific and Technical Guidelines (S&TG) of the Commission on the Limits of the Continental Shelf (CLCS). For the purposes of UNCLOS any kind of land mass of a coastal State may generate a continental margin to be delineated in accordance with Article 76. However, establishing the outer edge of the continental margin of islands located in active spreading mid-oceanic ridges settings may present a challenge to coastal States when following the methodology developed in the S&TG, which were established considering geological continental margins. This paper discusses how to distinguish the base of the continental slope (BOS) from the deep ocean floor for islands in active spreading mid-oceanic ridge settings within the legal framework provided by UNCLOS, taking into account the S&TG, and the summary of recommendations adopted so far by the CLCS.